Kconnect:The Design and Development of Versatile Web Portal for Enhanced Collaboration and Communication - Gupta, Anshula; Vardhan, Harsh; Varshney, Sakshee; Saxena, Shivi; Singh, Sandhya; Agarwal, Nidhi (EAI Endorsed Transactions on Scalable Information Systems, 2023)
The design and creation of a web gateway to improve cooperation and communication among campus communities are discussed in this essay. The portal is designed to be flexible and adaptive to various user groups and their unique requirements. The writers discuss the numerous features and functionalities integrated into the portal as well as the user-centered design methodology they utilised to construct it. The site has resources for resource management, event planning, group communication, and information exchange. The writers also go through the difficulties that were experienced during creation and make suggestions for future advancements. Overall, the online portal offers a useful setting for campus communities to communicate and work together. As we all know that pandemic has brought a huge change in everyone’s life and work from home has become THE NEW NORMAL. One of its drawback is the lack of interaction among peers. This hinders the flow of information in the hierarchy. In order to cope up with this problem, we have come up with a solution “KCONNECT” that aspires to bridge the communication gap. KConnect is a networking platform that will help students to connect with each other and gain relevant knowledge about new opportunities regarding career, scholarships, club activities and higher studies. The results of the study show the implementation of a web portal as an effective way to allow students increase connections and stay updated.